2019
DOI: 10.1002/tax.12026
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic species in an ancient flowering‐plant lineage (Hydatellaceae, Nymphaeales) revealed by molecular and micromorphological data

Abstract: The flora of the southwestern Australian biodiversity hotspot is rich in endemic species, many of which remain to be discovered or properly described; estimates of species diversity and levels of endemism should take into account the possible occurrence of cryptic species. Here we explore taxonomic diversity in a Western Australian lineage belonging to the primarily Australian genus Trithuria, the sole genus of Hydatellaceae (Nymphaeales). Recent molecular evidence supports the existence of cryptic species in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 73 publications
(93 reference statements)
0
10
0
Order By: Relevance
“…For example, the inclusion of one representative of each of the four sections of the genus Trithuria could be included in future investigations in order minimize the level of homoplasy between the divergent family of Hydatellaceae and the rest of the plant order. Such an inclusion would also benefit the ongoing evaluation of the species diversity of Hydatellaceae, which was recently reported as strongly underestimated [58].…”
Section: Outgroup Selectionmentioning
confidence: 99%
“…For example, the inclusion of one representative of each of the four sections of the genus Trithuria could be included in future investigations in order minimize the level of homoplasy between the divergent family of Hydatellaceae and the rest of the plant order. Such an inclusion would also benefit the ongoing evaluation of the species diversity of Hydatellaceae, which was recently reported as strongly underestimated [58].…”
Section: Outgroup Selectionmentioning
confidence: 99%
“…In their new article Sokoloff et al (2019) reported the existence of cryptic species among self-pollinating members of Trithuria sect. Trithuria and sect.…”
Section: Trithuria In New Zealand: One Species or Two?mentioning
confidence: 99%
“…In particular, they demonstrated, using evidence from microsatellite data (SSRs), an expanded molecular phylogenetic analysis, and fruit micromorphology, that Western Australian plants currently classified as T. australis sensu lato (sect. Hydatella) in fact belong to at least four species; of those four newly detected entities, one was formally described as a new species, Sokoloff et al (2019) concluded that species diversity in Hydatellaceae is strongly underestimated. These findings are well in line with our proposed treatment of the South Island Trithuria as a distinct species.…”
Section: Trithuria In New Zealand: One Species or Two?mentioning
confidence: 99%
See 2 more Smart Citations